Microstructure and Mechanical Properties of as-soldered SnBi-SACBN Composite Solder Paste - FU Hai-feng; LIU Yang; SUN Feng-lian; ZHANG Hao; WANG Min (Journal of Harbin University of Science and Technology)
Aiming at the brittleness of Sn58Bi ( SnBi) solder joints，the SnBi composite pastes were prepared by mechanical mixing method with SAC-Bi-Ni ( SACBN) alloy powder. The concentration of the additives was 0， 0. 5，1，and 5 wt%，respectively. The microstructure and composition of the as-soldered alloys were investigated by SEM. Meanwhile，the mechanical properties of the alloys were characterized by nanoindentation method. Experimental results indicate that with the increase of the SACBN content in the composite solder pastes，the concentration of β-Sn phase increased. In contrast，Bi-rich phase was reduced after reflow. The refined reticular structure of Bi-rich phase was suppressed in the alloys. As the increase of SACBN particles increased from 0 to 5 wt%，the hardness of the alloy decreased from 219. 05 N/mm2 to 174. 18 N/mm2. Meanwhile，the elastic modulus decreased from 5. 93 N/mm2 to 2. 86 N/mm2.